Regional Monetary Integration among Developing Countries: New Opportunities for Macroeconomic Stability beyond the Theory of Optimum Currency Areas? - Barbara Fritz; Laurissa Mühlich (German Institute of Global and Area Studies (GIGA), 2006)
Optimum Currency Area (OCA) approaches turn to be inadequate in the analysis of the new regional monetary integration schemes that have sprung up among developing and emerging market economies. Instead, in accordance with the concept of 'original sin' (Eichengreen et al.) we argue that regional monetary South-South integration schemes that, unlike North-South arrangements, involve none of the international reserve currencies, have specific monetary constraints and implications which need to be duly considered. A first comparative analysis of three cases of monetary South-South cooperation in South Africa (CMA), East Asia (ASEAN) and Latin America (Mercosur) shows that these can indeed provide macroeconomic stability gains but that this strongly depends on the existence of economic hierarchies within these integration schemes. – – Theoretische Ansätze zum Optimalen Währungsraum erweisen sich als unzureichend, wenn es um die Analyse monetärer Integrationsprojekte geht, die in jüngster Zeit zwischen Entwicklungs- und Schwellenländern entstanden sind. In Anlehnung an das Konzept des 'original sin' (Eichengreen et al.) argumentieren wir, dass regionale monetäre Süd-Süd-Integrationsarrangements, die im Gegensatz zu Nord-Süd-Integrationen keine der internationalen Reservewährungen mit einbeziehen, spezifischen monetären Beschränkungen unterliegen, deren systematische Berücksichtigung innerhalb der Theorie Monetärer Integration bisher weitgehend fehlt. Eine erste vergleichende Analyse von drei Fällen monetärer Süd-Süd-Kooperation im Südlichen Afrika (CMA), Ostasien (ASEAN) und Lateinamerika (Mercosur) zeigt, dass diese tatsächlich makroökonomische Stabilitätsgewinne mit sich bringen, die aber in hohem Maße von der Existenz interner ökonomischer Hierarchien innerhalb dieser Integrationsräume abhängen.
Keywords: F33; F36; O11; 330; regional monetary integration; monetary integration theory; development theory; ASEAN; Mercosur; CMA; Währungsraum; Optimaler Währungsraum; Süd-Süd-Beziehungen; Ökonomische Sicherheit; Südliches Afrika; ASEAN-Staaten; MERCOSUR-Staaten